State Civil Apparatus Salaries and Patents as Joint Property Post-Divorce Perspective of Government Rules And Islamic Law - Rahmad Fauzi Salim; Dhiauddin Tanjung (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze government regulations and Islamic law regarding the salary status of state civil servants and patents as joint property after divorce. The government regulation in question is Government Regulation Number 45 of 1990 concerning Amendments to Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants. This research uses a qualitative method based on normative juridical. In addition to government regulations which are the source of data, this study also uses the maqahid syar'iyah view. The two data sources are then compared and then formulated into one concept. The results of the study explain that divorce based on Article 3 of Government Regulation Number 45 of 1990 concerning Amendments to Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants, it is said that an state civil apparatus divorce must go through the permission of a superior. And according to article 37 and article 49 of Law Number 1 of 1974 it is said that joint assets in the event of a divorce are divided according to existing legal regulations, and article 49 says that the Religious Courts have the duty and authority to examine, decide and resolve cases at the national level. The first is between people who are Muslim in the field of settlement of joint assets.